Molecular gastronomy in function of scientific implementation in practice - Slobodan Ivanovic; Kresimir Mikinac; Luka Perman (UTMS Journal of Economics, 2011)
Modern culinary direction - molecular gastronomy is very complex, and the relative youth of that direction affects the ignorance of the matter by a large number of professionals and the general public. It is precisely this lack of matter which causes a number of disagreements between chefs and scientists, while there is a number of related debates about aspects of molecular gastronomy, especially in connection with a change in its gastronomic cuisine. The main focus of disagreement lies in the name of "molecular", which mostly leads to a misunderstanding, because of the identification with something microscopic. A very common mistake is to address this branch of gastronomy as a style of cooking, which she doesn't represent. The second mistake is naming its practical application of molecular cooking, molecular cuisine. Molecular gastronomy is a scientific discipline that studies food and asks questions and gives answers so far unanswered questions about gastronomy. Simply put, molecular gastronomy can be understood as a process of application of science in everyday cooking, and the application of molecular gastronomy in the kitchen. Modern man with his awareness made some chefs to reconsider the adoption of these radical ideas to accomplish the fusion of science and gastronomy. This idea is established as a full hit, because today the best restaurants in the world, the vast majority of those who have seen the benefits of these two joints before incompatible branches of human activity. As a culinary direction it quickly spread to Western Europe and North America, and it later spread to other parts of the world, but Croatia and neighboring countries are not one of them. Molecular gastronomy shows the trends of further progress, and in the future molecular gastronomy will be more prevalent and popular.
Keywords: L66; 330; molecular gastronomy; inovation; gastronomy trends